Experimental investigation of interfacial mass transfer mechanisms for a confined high‐reynolds‐number bubble rising in a thin gap. Issue 6 (28th November 2016) - Roudet, Matthieu; Billet, Anne‐Marie; Cazin, Sébastien; Risso, Frédéric; Roig, Véronique
Abstract : Interfacial mass transfer is known to be enhanced for confined bubbles due to the efficiency of the transfer in the thin liquid films between them and the wall. In the present experimental investigation, the mechanisms of gas–liquid mass transfer are studied for isolated bubbles rising at high Reynolds number in a thin gap. A planar laser induced fluorescence (PLIF) technique is applied with a dye the fluorescence of which is quenched by dissolved oxygen. The aim is to measure the interfacial mass fluxes for pure oxygen bubbles of various shapes and paths rising in water at rest. In the wakes of the bubbles, patterns due to the presence of dissolved oxygen are observed on PLIF images. They reveal the contrasted contributions to mass transfer of two different regions of the interface. The flow around a bubble consists of both two thin liquid films between the bubble and the walls of the cell and an external high‐Reynolds‐number in‐plane flow surrounding the bubble. Mass transfer mechanisms associated to both regions are discussed. Measurement of the concentration of dissolved oxygen is a difficult task due to the nonlinear relation between the fluorescence intensity and the concentration in the gap. It is however possible to accurately measure the global mass flux transferred through the bubble interface. It is determined from the fluorescence intensity recorded in the wakes when the oxygen distribution has been made homogeneous through the gap by diffusion. Assuming a reasonable distribution of oxygen concentration through the gap at short time also allows a measurement of the mass fluxes due to the liquid films. A discussion of the results points out the specific physics of mass transfer for bubbles confined between two plates as compared to bubbles free to move in unconfined flows. © 2016 American Institute of Chemical Engineers AIChE J, 63: 2394–2408, 2017